Sistemas de reservatórios em série : respostas ecológicas à fragmentação de habitat e alteração do regime de fluxo. - Santos, Natália Carneiro Lacerda dos (2016)
The number of dams has had a significant increase in the last six decades, altering the physiography of rivers and creating systems of reservoirs in series, with severe modifications on physical-chemical parameters, connectivity patterns, system productivity, environmental services and communities structure. Most of the research of fresh water ecosystems affected have focus on isolated reservoirs, neglecting the cumulative effect of multiple dams in a hydrographic basin. The goal of this research was to investigate the effects of modifications imposed by reservoir cascades on biological communities. First, I aimed on investigating whether reservoirs disposed in a cascade function as environmental filters for fish life history tracts. Different environmental variables obtained at local and regional scales were used to characterize longitudinal variation. Six life history tracts were selected for fish species (diet, migration, fecundation, parental care, position on the water column and body size). The results pointed to a higher influence of regional environmental variables, such as the position of the reservoir in the cascade, area, length and time of water residence in the determination of tracts, with the evidence of reduction of migratory species and a fauna mainly composed by small sized fish on the reservoirs situated on the high portions of the cascade. Lastly, I aimed on investigating the relative role of different predictors of hydrologic regime alteration (changes of physical-chemical variables, Accumulated Volume and connectivity rupture) over three biologic communities. In accordance with partitioning variation, the relevance of the predictors variables varies depending on the community analyzed. Environmental and accumulated volume variables strongly explained part of the variation on community structure of phytoplankton, while for benthonic macroinvertebrates no important effects were reported. For fish communities all the predictor variables were important, presenting expressive values of shared fractions, indicating that, in general, effects are associated.